Evaluation of Microbial Load in Fast Food Establishments in Kaduna Metropolis: A Descriptive Cross-sectional Study - Usman, Suleiman; Afolabi, Opasola O.; Modupe, Lateefat H. (Issues and Development in Health Research Vol. 5, 2021)
The increase in human population brings about the proliferation of more food manufacturing and dispensing establishments among which are fast food establishments and food vendors or street hawkers in Nigeria. Fast food establishment’s indiscriminate activities are often associated with frequent food poisoning in developing countries especially in Nigeria. This scenario could be due to the poor state of food safety and general hygiene in these countries. Consequently, large quantities of food produced and distributed get to the consumer in an unwholesome condition. The contamination of food could be due to a variety of microbial pathogens, chemicals, and parasites that may find their way into the food chain at different points during the food preparation and production process. This study evaluates the microbial load in some selected fast food establishments in Kaduna Metropolis, Kaduna state, Nigeria. Thus, five research objectives and questions guided the study. A descriptive cross-sectional study using a multistage sampling technique was adopted to select 174 fast-food establishments. The premises were assessed on the practice of personal hygiene and implementation of Hazard Analysis and Critical Control Point (HACCP) principles during their food preparations. Laboratory analyses were carried out on the samples for bacteriological analyses of 1g of food (Tuwon Shinkafa, Tuwon Masara, Stew, Rice, and Bread). The study found that majority of the selected fast food establishments were observed to have Predominates bacterial isolates that include Pseudomonas spp. (50%), Salmonella spp. (86.7%), Shigella dysenteries (68.7%), Escherichia coli (20.0%) and Staphylococcus aureus (97.3%) respectively. The total number of occurrence of bacteria in all the food sampled was 2,659 cfu/g with Bread having the highest number of 685 cfu/g followed by Tuwon Masara with 629 cfu/g. The study equally found out that Staphylococcus aureus appears the highest in the samples with 700 cfu/g followed by Salmonella with 629 cfu/g. Hence, the predominant occurrence of bacteria in the food samples is due to poor personal hygiene, environmental sanitation and general cleanliness of the eating utensils which was observed during the study. It is recommended that health education of the food handlers on personal hygiene and HACCP implementation should be given more priority in Kaduna metropolis.